Grice's Café: coffee, cream, and metaphor comprehension - Genovesi, Chris (Frontiers in Communication, 2023)
Some theorists argue that Grice’s account of metaphor is intended as a rational reconstruction of a more general inferential process of linguistic communication (i.e., conversational implicature). However, there is a multi-source trend which treats Grice’s remarks on metaphor as unabashedly psychological. The psychologized version of Grice’s view runs in serial: compute what is said; reject what is said as contextually inappropriate; run pragmatic processing to recover contextually appropriate meaning. Citing data from reaction time studies, critics reject Grice’s project as psychologically implausible. The alternative model does not rely on serial processing or input from what is said (i.e., literal meaning). I argue the serial processing model and its criticisms turn on a misunderstanding of Grice’s account. My aim is not to defend Grice’s account of metaphor per se, but to reinterpret auxiliary hypotheses attributed to him. I motivate two points in relation to my reinterpretation. The first point concerns the relationship between competence and performance-based models. To the second point: Several of the reinterpreted hypotheses make predictions that are largely consistent with psycho neurolinguistic data.